State of the Art Laryngeal Imaging: Research and Clinical Implications - Deliyski, Dimitar D. (2010)
PURPOSE OF REVIEW: This paper provides a review of the latest advances in videostroboscopy, videokymography and high-speed videoendoscopy, and outlines the development of new laryngeal imaging modalities based on optical coherence tomography, laser depth-kymography, and magnetic resonance imaging, published in the past 2 years. RECENT FINDINGS: VIDEOSTROBOSCOPY AND VIDEOKYMOGRAPHY: Image quality has improved and several image processing and measurement techniques have been published. HIGH-SPEED VIDEOENDOSCOPY: Significant progress has been made through increased sensitivity and frame rates of the cameras, and the development of facilitative playbacks, phonovibrography and several image segmentation and measurement methods. Clinical evidence was presented through applications in phonosurgery, comparisons with videostroboscopy, normative data, and better understanding of voice production. OPTICAL COHERENCE TOMOGRAPHY: Latest developments allow for the capture of dynamic high resolution cross-sectional images of the vibrating vocal fold mucosa during phonation. DEPTH-KYMOGRAPHY: New laser technique allowing recording of the vertical movements of the vocal folds during phonation in calibrated spatial values. LARYNGEAL MAGNETIC RESONANCE: New methods allow high-resolution imaging of laryngeal tissue microstructure, or measuring of dynamic laryngeal structures during phonation. SUMMARY: The endoscopic laryngeal imaging techniques have made significant advances increasing their clinical value, while techniques providing new types of potentially clinically-relevant information have emerged.